Peranan Komite Olahraga Nasional Indonesia Provinsi Jambi dalam Pembinaan dan Pengembangan Olahraga Panahan - Masriyani, Masriyani; Nuraini, Nuraini; Putri, Rizky (Wajah Hukum, 2025)
Sport is a basic need for every human being and plays an important role in life. Physical activity is a characteristic of life, indicating that every individual needs movement for health and well-being. In this context, the role of the Indonesian National Sports Committee (KONI) in developing sports activities. One of the sports that cannot be ignored is archery, which has the potential to achieve proud achievements at the national and international levels. This study aims to analyze the role of KONI in developing archery athletes in Jambi Province, to unravel the obstacles faced in the coaching process, and to find solutions to overcome these obstacles. In this study, the method used is empirical juridical with a Socio-legal research approach. From the results of the study, it was concluded that KONI has made efforts to develop archery athletes, but has not been optimal. The obstacles faced are limited training facilities and infrastructure, which are caused by a lack of budget and minimal funding, less than optimal program assistance. Efforts made by KONI Jambi Province are to improve the budget system by submitting a budget plan in accordance with Regional Regulations, so that the needs of sports facilities and infrastructure can be met properly, it is important to plan independent funding sources for KONI. This study also recommends several strategic steps for KONI to support its role in the development and development of archery in an effort to increase the achievements and number of athletes at various levels, so that the achievements can be maximized.